STUDY ON ECOLOGY OF RED EYE SNAIL (Cerithidea obtusa) AT JANGKANG RIVER ESTUARY ECOSYSTEM OF SELAT BARU VILLAGE DISTRICT OF BENGKALIS RIAU PROVINCE - Nurliya '; Syafruddin Nasution; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study was conducted in April-May 2016. Samples were taken in the mangrove forest in the village of New Straits Bengkalis. The aim of this study was to determine the ecological parameter of red eye snail (C. obtusa), which include population density, size distribution of the individuals, as well as the relationship between the organic content of the sediment and density of snail. The method used in this research was survey method. Research station consists of two stations, which ware determined purposively. There were three zones each station, and each zone consist of three plots. Each plot divided in to 9 sub-plots measuring 1x1m2. Results showed that the average density of red eye snail in the station I was higher (39.22 ind / m2) than the density on stations II (21.66 ind / m2). However, statistical analysis (T test) was known that density between two stations were not significantly different. The dominant size group of C. obtusa in the area was the forth class (2,89-3,33 cm), while the less dominan was the first class (< 1,6 cm). Linier regression analysis showed that there was a medium value of relationship between sediment organic matter versus the density of C. obtusa r = 0.423.Keywords : Density, Cerithidea obtusa, Organic sediment, Jangkang Estuary.